The Conditions for Benefiting from the Internal Audit's Cognitive and Decision-Making Potential in the Accounting Information System (AIS) - Szymczyk-Madej, Katarzyna (Warunki wykorzystania możliwości poznawczych i decyzyjnych audytu wewnętrznego w systemie informatycznym rachunkowości, 2011)
The paper describes the internal audit's information potential, focusing on cognitive and decision-related information. The author identifies the conditions to be met to use such information effectively. The discussed conditions are related to organizational, psychological and social factors as well as to such areas as competences, communication, law and finance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 170-178
Keywords: accounting information system; internal audit; internal control